Cut flowers : a study of major markets (ITC GenevaCL, 1997)
Presents a market study of fresh cut flowers in Germany, France, UK, Netherlands, Switzerland and USA. Reviews products that are of special interest to developing countries wishing to develop an export-oriented floricultural industry.
Keywords: FLOWERS